Precautionary measures in Brazilian Criminal Procedure : reform with Law No. 12.403/2011 (Revista do Tribunal Regional Federal da 3ª Região, 2012)
Law no. 12. 403/2011, which amended Title IX of the Code of Criminal Procedure, brought significant changes to the Brazilian legal system with regard to criminal procedural precautionary measures, especially with regard to the requirements for granting them, broadening them on the one hand - to allow them to be better adapted to the perpetrator of the crime, according to the seriousness of the crime and its real need for investigation or criminal investigation, for the application of the law and as a disincentive to new practices - and, on the other hand, restricting the hypotheses of granting precautionary prisons, according to quantitative criteria of penalties. However, although it seems clear that the new measures generally seek to prioritize the restriction of rights over custody in a penal institution, some of them appear to be difficult, or almost impossible, to comply with and/or monitor. It is not too much to point out from the outset that a precautionary measure applied and not complied with, without the state's supervision, renders it innocuous and ineffective, as well as demoralizing the state itself. If precautionary measures were introduced into the legal system with the aim of avoiding unnecessary imprisonment, it is essential that they are effectively enforced with the utmost rigor in order to achieve their objective.Translated with DeepL.com (free version)
Keywords: pre-trial detention; Law no. 12.403/2011; gravity of the fact